The Relationship of Clinical Instructure Motivation with the Implementation of Preceptorship in dr. Soeselo Slawi Hospital - Ikawati Setyaningrum; Firman Hidayat; Ratna Widhiastuti (Universitas Muhammadiyah Tangerang, 2020)
Preceptorship is one method of guidance with one to one relationship in the scope of nursing which is considered good enough to add skills in care, both soft skills, hard skills and attitude of the nursing profession. Many factors affect the implementation of preceptorsip in hospitals. This study aims to determine the relationship between clinical instructional motivation and the implementation of preseptorship at Dr. Soeselo Slawi. This research is a quantitative study and the type of descriptive correlation research design with cross sectional approach. The sampling technique used was a total sampling of 39 people. The research instrument uses a motivation questionnaire containing 26 statements, whereas for Preceptorship uses a questionnaire containing 10 statements. Chi square analysis results showed that the p value was 0.007 (<0.005), which means there was a significant relationship between CI motivation and the implementation of Preseptorship. The hospital is expected to be able to choose nurses who will become CIs according to certain competency and knowledge standards, as well as specializing CI assignments so that they do not overlap with patient service tasks. Keywords: Motivation. Clinical instructure, preceptorship